Rapid microfluidic separation of magnetic beads through dielectrophoresis and magnetophoresis - Krishnan, Jegatha Nambi; Kim, Choong; Park, Hyun Jik; Kang, Ji Yoon; Kim, Tae Song; Kim, Sang Kyung (WILEY, 2009)
We present the design and fabrication of a new microfluidic device in which the dielectrophoresis and magnetophoresis phenomena were used for the separation of the superparamagnetic microbeads of different sizes. By exploiting the fact that two different particles can exhibit different dielectrophoretic force-frequency spectra, we utilize this device to perform multiplex detection from a single sample solution. We found the transition frequency range for 1, 2.8, and 4.5 mu m magnetic beads using our device. Bead-based analysis revealed that a high separation efficiency (similar to 90%) could be obtained from a single sample solution containing both 4.5 and 2.8 mu m beads. The average flow velocity of the beads was maintained at 9.8 mm/s, enabling fast analysis with a smaller amount of reagents. The magnetic field distribution on the beads and the bead flow at the channel cross section for different dielectrophoretic conditions was obtained using CFD-ACE(+) simulation. Issues relating to the fabrication and operation of the device are discussed in detail. Finally, we demonstrated the feasibility of parallel detection/trapping of different beads on the same chip. This separation approach offers the performance of multiplex analysis in lab-on-a-chip devices.
Keywords: ON-CHIP